2022
DOI: 10.3390/mi13081341
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and Heat Transfer Performance of Mini-Grooved Flat Heat Pipe Filled with Different Working Fluids

Abstract: Mini-grooved flat heat pipe (MGFHP) possesses the advantages of high compactness, no mechanical component, super thermal conductivity, and excellent temperature uniformity, which can meet the demand for electronic devices efficiently cooling. In this research, visual and heat transfer experiments were performed to investigate the flow and thermal characteristics inside the MGFHP. Fluid flow and distribution are observed to be quite different in the MGFHP containing different working fluids, which is affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore, it can be inferred that the effect of evaporation on the capillary performance parameters of copper foams can be neglected. However, the values of K/reff obtained by Equations ( 15) and ( 17) are significantly smaller than that obtained by Equation (18). It can be inferred that gravity plays an important role in the capillary performance parameters of copper foams.…”
Section: Analysis Of Experiments Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, it can be inferred that the effect of evaporation on the capillary performance parameters of copper foams can be neglected. However, the values of K/reff obtained by Equations ( 15) and ( 17) are significantly smaller than that obtained by Equation (18). It can be inferred that gravity plays an important role in the capillary performance parameters of copper foams.…”
Section: Analysis Of Experiments Resultsmentioning
confidence: 67%
“…The experimental results showed that the heat transportation capability is up to ten times higher than those of the metal plate and the conventional wickless heat-pipe plates. Xin et al [18] studied the flow and thermal characteristics in a mini-grooved flat heat pipe.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the relatively low cost of FMHPs, the low dimensions, and high heat flux dissipation power, the literature [2] shows that FMHPs have various typical applications of microelectronic devices. According to [3], electronic devices work at temperatures usually between −5 ÷ 65 • C, but recently, the maximum heat flux in these components is increasing more and more, reaching maximum temperatures of 70 ÷ 80 • C. Increases above a certain threshold can cause functional instability or even destruction of electronic devices. To avoid this, one of the cooling methods uses thermal tubes.…”
Section: Introductionmentioning
confidence: 99%